The preparation of hierarchical SAPO-34 crystals via post-synthesis fluoride etching - Chen, Xiaoxin; Vicente, Aurélie; Qin, Zhengxing; Ruaux, Valérie; Gilson, Jean-Pierre; Valtchev, Valentin (Chemical communications (Cambridge, England), 2016)
SAPO-34 crystals are etched in fluoride medium. The interface between crystalline domains is dissolved and yields a hierarchical material with a system of straight intersecting mesopores that improve the access to micropore space.